Atmospheric chemistry of HFE-7000 (i-C3F7OCH3) and isofluoro-propyl formate (i-C3F7OC(O)H): reactions with OH radicals, atmospheric lifetime and fate of alkoxy radical (i-C3F7OCH2O) – a DFT study. (3rd March 2016) - Mishra, Bhupesh Kumar; Gour, Nand Kishor; Bhattacharjee, Debajyoti; Deka, Ramesh Chandra
ABSTRACT: The mechanism of hydrogen abstraction reaction between HFE-7000 (i-C3 F7 OCH3 ) and OH radicals using M06-2X functional in conjunction with 6-31+G(d, p) basis set is investigated. The pre-reactive and post-reactive complexes from intrinsic reaction coordinate calculations are validated at entrance and exit channels, respectively. The standard enthalpies of formation for the species and bond dissociation energy for C–H bond are also estimated. The rate constants of the titled reactions over the temperature range of 250–450 K are reported. The OH-driven atmospheric life time of i-HFE-7000 is computed to be 3.19 years. The atmospheric fate of the alkoxy radical (i-C3 F7 OCH2 O ) is also explored here for the first time. Three prominent plausible decomposition channels including oxidation are considered in detail. The thermochemical data reveal that reaction with O2 is the dominant path for the decomposition of i-C3 F7 OCH2 O radical. Moreover, rate constant for the OH-initiated hydrogen abstraction of isofluoro-propyl formate (i-C3 F7 OC(O)H) is also reported. Graphical Abstract: